Amino-functionalized hydrogel immobilized microbial consortia to reduce the dissemination risks of antibiotic resistance genes in soil - Yongxin Guo; Jiaoyang Ji; Xianfeng Lin; Yanjun Li; Gang Wang; Yong Yu (Bioresource Technology, 2026)

Highly fluorescent Cucurbit[7]uril covalent organic frameworks for fluorescence sensor array - Nurimangul Muntiza; Qun Wang; Yanan Liu; Jiayi Wang; Xuejia Chang; Meifang Xiao; Boyu Yuan; Qinran Li; Haijie Li; Yanjun Yu; Qiliang Deng (Analytica Chimica Acta, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Study on the selective crushing behavior and mechanism of Dahongliutan spodumene ore under high-pressure grinding roll (HPGR) - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Oxidation patterns and stability mechanisms of marine oils revealed by oxidized triglyceride and phospholipid analysis using RPLC–Q-TOF - Nan Meng; Yaru Li; Peixu Cong; Yu Song; Yanjun Liu; Jie Xu; Changhu Xue (Food Research International, 2026)

Critical overview of Peracetic acid-based advanced oxidation processes: Evolution, fundamentals and water treatment applications - Yongbo Yu; Jiaxin Yu; Haochen Zhang; Yongchao Mu; Yanjun Xin; Bin Zhang; Jun Ma (Chemical Engineering Journal, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Disrupting the cardiolipin oxidation-apoptosis axis: low-temperature, high-salinity depuration extends anhydrous storage in Pacific oysters - Nan Meng; Xinyu Cao; Yu Song; Peixu Cong; Yanjun Liu; Yi Liu; Changhu Xue; Jie Xu (Food Research International, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Stage-specific estimation of rice leaf area index and above-ground biomass from UAV LiDAR-derived structural features - Zhongyu Jin; Yanjun Wang; Juchi Bai; Zhonghui Guo; Shilong Li; Fenghua Yu; Tongyu Xu (Computers and Electronics in Agriculture, 2026)

NearStitch: Robust near-surface image stitching for phenotyping - Yu Wang; Shichao Jin; Jianling Tang; Ke Wang; Shan Xu; Yanjun Su; Qinghua Guo; Dong Jiang; Yanfeng Ding; Frédéric Baret (Computers and Electronics in Agriculture, 2026)

Effect of laponite treatment on liquefaction-induced tunnel uplift: Evaluation based on multiple intensity measures - Jinghua Zhang; Yong Chen; Emilio Bilotta; Yuan Xie; Yanjun Xu; Yong Yuan; Haitao Yu; Qing Sun (Transportation Geotechnics, 2026)

Sparse hierarchical recurrent modeling for real-time grade prediction in hydrogen-based hematite transformation: modeling and industrial validation - Tianyou Yu; Anh Nguyen; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Mechanism of EPFRs formation from hydroquinone on transition metal oxide surfaces: coupled experimental and density functional theory study - Junyao Fu; Lingqin Zhao; Aijia Zhang; Guohao Yang; Fan Yu; Yanjun Hu (Waste Disposal & Sustainable Energy, 2026)

Isomucronulatol attenuates liver aging by inhibiting GSK-3β acetylation and promoting β-catenin accumulation - Peiyao Chen; Baolian Wan; Fei Yu; Yanqiu Zhang; Mengmeng He; Enyi Wu; Yanjun He; Hui Zhong; Hao Zhang (Journal of Natural Medicines, 2026)

Experimental Study on the Extreme Wave Run-Up Phenomenon of a Semi-Braceless Floating Wind Turbine Foundation Under Focusing Waves - Yanjun Mao; Yu-Fei Wu; Xiaoxu Huang; Xiaozhou Ma; Guohai Dong (Oceans, 2026)
A series of physical model tests of a semi-braceless floating wind turbine foundation (FOWT) under freak waves was conducted in the present work. The extreme wave run-up phenomenon on the FOWT columns was reported and investigated. The back column exhibits a median wave run-up amplification factor of 1.65 (a 65% rise from the baseline condition), with the maximum recorded value hitting 3.18, marking a 218% amplification compared to the reference wave run-up. Four factors contribute to this phenomenon, including the wave-trapped mode between columns, the shoaling effect of the pontoons, the relative motion between the platform and the wave surface, and nonlinear wave run-up. The extreme wave run-up corresponds to violent wave dynamic pressures, showing nonlinear column pressure distributions. Steeper local freak waves can lead to higher wave dynamic pressures on the columns, and slamming pressures occur under breaking waves in some harsh wave conditions. The peak slamming pressure on the back column reaches 300% of that on other columns. The wave run-up and wave pressures on the columns are relevant to the structure’s load level, which is crucial to the safety of the engineering design.

Kinetic mechanism and structural evolution during blank roasting of vanadium-bearing shale - Xiaolong Yu; Jianping Jin; Xinran Zhu; Zhe Bai; Shuaihou Yang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Elucidating the oxidation mechanism of phospholipid-based marine oils during storage: A new insight based on the analysis of oxidized phospholipids - Nan Meng; Peixu Cong; Xincen Wang; Yu Song; Yanjun Liu; Yaru Li; Jie Xu; Changhu Xue (Food Research International, 2026)

Investigating the molecular mechanism of plasmalogen and quality changes in Pacific oyster (Crassostrea gigas) depurated under salinity stress - Yu Song; Lili Hao; Xincen Wang; Peixu Cong; Yanjun Liu; Xiaoxu Wang; Zhaojie Li; Changhu Xue; Jie Xu (Food Research International, 2026)

Molten salt-assisted Co-pyrolysis of biomass and waste plastics: Analysis of product characteristics - Yanjun Hu; Chong Yang; Fan Yu; Qianqian Guo; Xingxuan Zhang; Wei Bao; Kitae Baek; Rufei Lu; Frederik Ronsse (Biomass and Bioenergy, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hydrogen-based fluidized bed reduction of limonitic laterite nickel ore: towards co-recovery of iron and nickel and metallization enhancement - Jiaqi Wang; Yanjun Li; Jianwen Yu; Yuexin Han; Jianping Jin (Minerals Engineering, 2026)

Migration and transformation pathways of Alkali/Alkaline earth metals and chlorine during co-gasification of biochar and Coal: An experimental and thermodynamic analysis - Qianqian Guo; Hongtao Liu; Yanjun Hu; Lu Ding; Long Jiao; Shuai Liu; Xu Wang; Lingqin Zhao; Fan Yu (Fuel, 2026)

A pH/heating-driven curdlan-based complementary hydrogel for promoting full-thickness skin wound healing - Qingchen Cui; Linrong Yu; Jiahe Miao; Yanjun Wei; ShanShan Du; Xianggen Wu (Carbohydrate Polymers, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Synergistic effect of cocatalyst engineering and radical regulation toward high selectivity in one-step methane conversion - Chuan Yu; Mingli Fu; Keke Tang; Yanjun Li; Lei Liu; Chen Yang; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Zircon textural and elemental evidence for the thermal state of the Carboniferous Oytag pluton in the West Kunlun Orogenic Belt, northwest China - Bingjin Yu; Yanjun Wang; Ying Wei; Shuilong Wang; Chuanlong Xu; Chengquan Wu; Weiguang Zhu; Chengbiao Leng (Acta Geochimica, 2026)

Performance analysis and experimental study of flexible opening-closing single garlic seed metering device based on DEM-MBD coupling - Zhengzhong Li; Hua Zhou; Yinping Zhang; Fangyuan Lu; Xian Wang; Jiaye Li; Yanjun Li; Yangting Hu; Rui Yu (Computers and Electronics in Agriculture, 2026)

SEC10 suppresses KLF15-mediated transcriptional activation of JAK1 and promotes BoHV-1 replication - Wenqing Ma; Xiao Yu; Yanan Xu; Fachao Sun; Mengrui Zhao; Xinlei Wang; Yanjun Huan; Xin Yin; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2026)

Comparison of dephosphorization processes for high-phosphorus oolitic hematite based on MLA mineralogical characteristic analysis - Yusen Yu; Wenbo Li; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

EPA-rich plasmalogen from Cucumaria frondosa enhances lipophagy by restoring lysosomal acidity via V-ATPase modulation - Zhigao Wang; Xiaoxu Wang; Xincen Wang; Yanjun Liu; Yu Song; Changhu Xue; Jie Xu (Food Bioscience, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Interfacial biomimetic engineering synergizing with mycelium: Constructing high-strength, water-resistant, and flame-retardant formaldehyde-free composites - Junqiang Shan; Yajuan Cao; Yanjun Chen; Yingye Shen; Tianpeng Chen; Yu Sha; Wenjun Sun; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Insight into the mechanism of natural preservatives (rosmarinic acid and phytic acid) against quality deterioration of Pacific white shrimp through interactions with hemocyanin - Junpeng Zeng; Xiaowei Fan; Junyi Song; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Sustainable hierarchical carbon architectures from bamboo for enhanced electromagnetic wave dissipation - Jiateng Chen; Minzhen Bao; Yu Wang; Weigang Zhang; Tiancheng Yuan; Yanjun Li (Environmental Research, 2026)

Endothelial Cell Differentiation-Related CircRNAs Drive the Differentiation of Vascular Endothelial Cells - Yu Sun; Zhuona Yin; Yidan Huang; Yanjun Chen; Hao Yin; Yuanmei Zhang; Wen Jin (Biochemical Genetics, 2026)

Mechanism of Cu migration and transformation during pyrolysis of Copper-Bearing sludge regulated by Cellulose/Kaolinite - Yanjun Hu; Xuan Yu; Lingqin Zhao; Qianqian Guo; Long Jiao; Fan Yu; Aijia Zhang (Waste Management, 2026)

Engineering Arabidopsis for improved yield and nutritional quality through heterologous expression of maize ZmERF118 gene - Zongjie Wang; Yang Zhao; Xinrui Ma; Yanjun Dong; Manyao Liu; Peng Jiao; Kaisheng Yu; Yimeng Wang; Yiyong Ma; Shuyan Guan (Plant Science, 2026)

Sustainable ironmaking via Hydrogen-based suspension pre-reduction of hematite: reduction mechanisms, bonding behavior, and comparison with carbon routes - Xuesong Sun; Yanjun Li; Jianwen Yu; Yize Guo; Yuexin Han (Minerals Engineering, 2026)

Microplastics affect the quality of Cucumis melo. L by regulating the jasmonic acid signaling pathway - Tianyu Liu; Jinpeng Zhang; Mao Xu; Zhengkun Zhang; Yanjun Li; Xuedong Tang; Ling Liu; Yong Yu (Environmental Pollution, 2026)

Corrigendum to “Ultrafast improvement of cellulose accessibility via non-dissolving pretreatment with LiBr·3H2O under room temperature” [Carbohydrate Polymers 284 (2022) 119180] - Zhonglei Huang; Guang Yu; Chao Liu; Meiyan Wu; Yanjun Tang; Bin Li; Hui Peng (Carbohydrate Polymers, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

Unraveling the flavor evolution mechanism in liquid-smoked rainbow trout through integrated lipidomics and flavoromics - Junpeng Zeng; Nan Meng; Xiaowei Fan; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Renewable, self-supporting bamboo-based composites for electromagnetic absorption and electrothermal management - Jiateng Chen; Yu Wang; Yanjun Li; Tiancheng Yuan (Environmental Research, 2026)

Transition from clear-water to biofloc systems improves growth, antioxidant response, and gene expression in Penaeus vannamei - Yanshuo Guo; Wenchang Liu; Yanjun Yu; Guozhi Luo; Hongxin Tan (Aquaculture, 2026)

A new method for efficient recovery of boron from boron-bearing iron concentrate: low-temperature fluidized selective reduction and magnetic separation - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2026)

Freeze-thaw differentially modulates the impact of agricultural film-derived microplastics on soil-crop system: Microbiome and metabolome responses - Yanjun Li; Jiayang Hu; Zhaojiang Liu; Yong Yu (Journal of Hazardous Materials, 2026)

Internal phosphorus loading and regulatory mechanism in China's largest urban lake: Implications for eutrophication management - Yuyi Wang; Chuanzhe Sun; Yanjun Wu; Gang Pan; Robert J.G. Mortimer; Fanyan Yang; Shuailong Wen; Suisui Zhang; Lejia Zong; Hezhong Yuan; Jianghua Yu; Jicheng Zhong (Journal of Environmental Management, 2026)

Facile synthesis of Fe3O4@wood-derived porous carbon with optimized impedance matching for enhanced microwave absorption performance - Jiateng Chen; Kaiwen Chen; Xinzhou Wang; Yu Wang; Yanjun Li; Tiancheng Yuan (Environmental Research, 2026)

Dual-bactericidal wood-reinforced hydrogel sensor for healthcare monitoring and information transmission - Hengyao Zhou; Hongwei Zhang; Yaobo Wang; Fanjun Yu; Yanjun Xie; Tianpeng Zhang; Zefang Xiao (Chemical Engineering Journal, 2026)

Thermal decomposition behavior of boron-bearing iron concentrate under nitrogen atmosphere: Kinetics, mineral phase transformation and microstructure evolution - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2025)

Formation of the Da'anhe reduced gold skarn in NE China: Evidence from U-Pb geochronology, and whole-rock and mineral geochemistry - Litian Zhang; Qihai Shu; Kai Xing; Fan Yu; Yanjun Wang; Zhonghai Zhao; Bing Li; Qingfei Wang; Jun Deng (Lithos, 2025)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Multi-quality attributes prediction and process parameter optimization of liquid-smoked rainbow trout by different machine learning models combined with genetic algorithm - Junpeng Zeng; Jingyi Luo; Yu Song; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Research International, 2025)

Effects of apoptosis on quality changes of Larimichthys crocea postmortem storage with emphasis on cytochrome c-mediated lipid deterioration - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Research International, 2025)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Harnessing enhanced rock weathering for carbon neutrality: potential and challenges in China - Lianghan Cong; Shuaiyi Lu; Pan Jiang; Tianqi Zheng; Yanjun Zhang; Xiaoshu Lü; Ziwang Yu; Tianfu Xu (Earth-Science Reviews, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Impact of Built Environment on Urban Vitality in Shrinking Cities: Moderating Effect of Housing Vacancy - Hui Fu; Guolei Zhou; Hongri Sun; Yu Jin; Hanchun Wu; Yanjun Liu (Chinese Geographical Science, 2025)

Identification of Ocean Thermal Energy Conversion Heat Exchange Model Based on Long Short-Term Memory Network and Heat Exchange Efficiency Improvement Study - Yanjun Liu; Xiu You; Mingqian Tian; Tianxu Zhang; Yun Chen; Yanni Yu (Journal of Marine Science and Engineering, 2025)
The core of ocean thermal energy conversion (OTEC) is the transfer and conversion of heat energy, and the heat exchanger is a key component of the heat transfer between the surface warm seawater and the lower cold seawater. The working fluid has a significant impact on the efficiency of the entire cycle in the temperature difference cycle. This study aimed to improve heat exchange efficiency. The article studied heat exchangers, used R134a as the circulating medium, and applied ANSYS-FLUENT 2020R2 simulation software to analyze the variation in heat transfer coefficients. We obtained the trend in the heat transfer coefficient of the heat exchanger with the shape of an elliptical tube under the condition of ocean temperature difference cycles. Then we used a long short-term memory network and Adam optimization algorithm to establish the prediction model. The NSGA-II 11 algorithm was used to realize optimization objectives of the highest heat transfer efficiency and the smallest cross-sectional area of heat transfer tubes along the X and Y directions. Finally, the parameters of the evaporator and condenser ultimately resulted in three optimal solutions. The results of this study can provide a certain theoretical basis and reference value for the efficiency analysis, structure optimization, and experimental research of the subsequent ocean differential circulation heat transfer.

Promising mass spectrometry imaging: exploring microscale insights in food - Xinyu Cao; Peixu Cong; Yu Song; Yanjun Liu; Changhu Xue; Jie Xu (Critical Reviews in Food Science and Nutrition, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

SenNet: A dual-branch image semantic segmentation network for wheat senescence evaluation and high-yielding variety screening - Jiaqi Yao; Shichao Jin; Jingrong Zang; Ruinan Zhang; Yu Wang; Yanjun Su; Qinghua Guo; Yanfeng Ding; Dong Jiang (Computers and Electronics in Agriculture, 2025)

Equivalency of DNA sequencing, HPTLC chromatographic analysis, botanical microscopy, for botanical identity/ authentication: A statistical evaluation and quantitation of identification uncertainty - Sidney Sudberg; Khanh Tran; Dinah Yu; Anthony Fontana; Robert LaBudde (Deceased); Zhengfei Lu; Yanjun Zhang; Adam Faller (Phytochemistry Letters, 2025)

Agricultural films derived microplastics intensify acetochlor toxicity on soil health - Zhaojiang Liu; Jiayang Hu; Yanjun Li; Yong Yu (Journal of Hazardous Materials, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Crustal thickness variation constraints on the Paleo-Tethyan orogenesis in the West Kunlun orogenic belt, China - Bingjin Yu; Yanjun Wang; Ying Wei; Chuanlong Xu; Chengquan Wu; Weiguang Zhu; Chengbiao Leng (Journal of Asian Earth Sciences, 2025)

PhenoSR: Enhancing organ-level phenotyping with super-resolution RGB UAV imagery for large-scale field experiments - Ruinan Zhang; Shichao Jin; Yi Wang; Jingrong Zang; Yu Wang; Ruofan Zhao; Yanjun Su; Jin Wu; Xiao Wang; Dong Jiang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Arsenic exposure, genetic susceptibility, lifestyle, and glucose-insulin homeostasis impairment: Revealing the association and interaction in a repeated-measures prospective study - Yongfang Zhang; Jiahao Song; Ming Zhang; Gaoyin Xiong; Yanjun Guo; Wei Liu; Linling Yu; Quanhong Liu; Yueru Yang; Shuhui Wan; Qing Liu; Zhiying Huo; et al. (Environmental Research, 2025)

Liquid–Liquid Phase Separation in Hereditary Hearing Loss - Kefan Tao; Yanjun Zong; Xiaozhou Liu; Xinyu Shi; Zhengdong Zhao; Yu Sun (Neuroscience Bulletin, 2025)

Enhanced pre-selection of spodumene via ultraviolet-induced fluorescence and improved YOLOv8 deep learning algorithm - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

The effect and mechanism analysis of calcium and magnesium between the blank roasting-leaching process of vanadium shale - Jianping Jin; Xiaolong Yu; Zhe Bai; Zhenya Zhou; Yuexin Han; Yanjun Li (Fuel, 2025)

Salting-induced lipid hydrolysis and oxidation in dried squid fillets: A mechanistic link to formaldehyde formation, color browning, and flavor alteration - Junpeng Zeng; Xiaowei Fan; Nan Meng; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Sediment transport evolution and impact on vegetation recovery in the Hanping village landslide–debris flow disaster chain in Shaanxi, China - Jiewei Zhan; Zhaowei Yao; Yanjun Shen; Da Huang; Zhaoyue Yu; Jianbing Peng (Ecological Engineering, 2025)

Multifunctional solar evaporation device integrating the advantages of azo COF and sunflower stalk for efficient pure water production and inactivation of pathogenic microorganisms in the residue - Jiayi Wang; Chenyu Li; Xuejia Chang; Yanfei Liu; Nurimangul Muntiza; Futai Lu; Yanjun Yu; Qiliang Deng (Chemical Engineering Journal, 2025)

Divergent Flowering Time Responses to Increasing Temperatures Are Associated With Transcriptome Plasticity and Epigenetic Modification Differences at FLC Promoter Region of Arabidopsis thaliana - Yu Han; Li Liu; Mengyu Lei; Wei Liu; Huan Si; Yan Ji; Qiao Du; Mingjia Zhu; Wenjia Zhang; Yifei Dai; Jianquan Liu; Yanjun Zan (Molecular Ecology, 2025)
Understanding the genetic, and transcriptomic changes that drive the phenotypic plasticity of fitness traits is a central question in evolutionary biology. In this study, we utilised 152 natural Swedish Arabidopsis thaliana accessions with re‐sequenced genomes, transcriptomes and methylomes and measured flowering times (FTs) under two temperature conditions (10°C and 16°C) to address this question. We revealed that the northern accessions exhibited advanced flowering in response to decreased temperature, whereas the southern accessions delayed their flowering, indicating a divergent flowering response. This contrast in flowering responses was associated with the isothermality of their native ranges, which potentially enables the northern accessions to complete their life cycle more rapidly in years with shorter growth seasons. At the transcriptome level, we observed extensive rewiring of gene co‐expression networks, with the expression of 25 core genes being associated with the mean FT and its plastic variation. Notably, variations in FLC expression sensitivity between northern and southern accessions were found to be associated with the divergence FT response. Further analysis suggests that FLC expression sensitivity is associated with differences in CG, CHG and CHH methylation at the promoter region. Overall, our study revealed the association between transcriptome plasticity and flowering time plasticity among different accessions, providing evidence for its relevance in ecological adaptation. These findings offer deeper insights into the genetics of rapid responses to environmental changes and ecological adaptation.

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

MiR-30d-5p Modulates Glucose and Lipid Metabolism by Targeting CD73 through the AMPK Pathway - Mingjie Song; Juan Wang; Wenli Mu; Yanwei Zheng; Yanjun Cai; Jing Liu; Yu Xia (Cell Biochemistry and Biophysics, 2025)

On the propagation arrest and crossover behavior of pipe bends under external overpressure - Zhenmian Li; Xiangyang Wang; Yanjun Wang; Mingze Huang; Yang Yu; Yaqian Zhao (Ocean Engineering, 2025)

Renewable bamboo-based composites for electromagnetic and thermal applications - Xiaolong Li; Haonan Ding; Yu Wang; Jinhai Guo; Yanjun Li; Tiancheng Yuan (Journal of Cleaner Production, 2025)

Preparation, identification and application of lipid-Maillard reaction products during the drying process of squid fillets - Junpeng Zeng; Xiaowei Fan; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Preparation of macroporous Cu-SSZ-13-supported MOx catalysts and their catalytic performance for the simultaneous removal of soot and NOx - Lanyi Wang; Yanjun Chen; Shiwei Wang; Xinyu Chen; Shengran Zhou; Jiahong Li; Di Yu; Chunlei Zhang; Siyu Gao; Xuehua Yu; Chengyang Yin; Xiaoqiang Fan; et al. (Chemical Engineering Journal, 2025)

Impact of anti-solvents on the characteristics of hemicellulose fractionated from bleached bamboo pulp using lithium bromide hydrates - Xuejing Yu; Runzhu Gong; Meiyan Wu; Yufa Gao; Qian Li; Fang Zhang; Mehdi Rahmaninia; Bin Li; Yanjun Tang (Carbohydrate Polymers, 2025)

Effects of microplastics on black soil health: A global meta-analysis - Zhaojiang Liu; Yanjun Li; Guanghui Xu; Yong Yu (Journal of Hazardous Materials, 2025)

The new insight into the impact of hemocyanin on quality deterioration of Pacific white shrimp during refrigerated storage - Xiaowei Fan; Junyi Song; Yu Song; Yanjun Liu; Junpeng Zeng; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Production of glycerylphosphorylcholine-enriched defatted egg yolk powder through integrated enzymatic and supercritical CO2 processing - Wen Yu; Luping Gu; Cuihua Chang; Yujie Su; Yi Wang; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

The catalytic activity of Ca/Fe-rich incineration ash in the pyrolysis of epidemic wood - Yanjun Hu; Zhenxing Luo; Long Jiao; Caimeng Yu; Jian Li; Qianqian Guo; Jian Song (Waste Disposal & Sustainable Energy, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Melatonin attenuates inflammatory bone loss by alleviating mitophagy and lactate production - Zexin Lin; Yuan Gu; Yingsong Liu; Zilin Chen; Shuai Fang; Zhuan Wang; Zixian Liu; Qingrong Lin; Yanjun Hu; Nan Jiang; Bin Yu; Guanqiao Liu (Apoptosis, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

An evaluation method of hydraulic fracture propagation behavior in rock containing natural fractures based on fractal dimension - Yulong Liu; Yanjun Zhang; Yuxiang Cheng; Ziwang Yu; Xuefeng Gao; Lei Liu (Geomechanics for Energy and the Environment, 2025)

Effects of mitochondrial lipidome alterations on quality deterioration of Larimichthys crocea postmortem storage: New insight from the perspective of mediating mitochondria-dependent apoptosis - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Insight into the mechanism of Maillard reaction and lipids mutually contribute to the flavor release of squid fillets during the drying process - Junpeng Zeng; Nan Meng; Yu Song; Xiaowei Fan; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2025)

True prevalence and spatial distribution of antibodies to Brucella spp. in goat populations in Hubei Province, People’s Republic of China: Progress toward disease elimination - Jie Pei; Yu Wang; Yanjun Zhou; Tao Huang; Jun Xie; Aizhen Guo; Yingyu Chen; Ian D. Robertson (Preventive Veterinary Medicine, 2025)

A clean and convenient way to utilize naturally air-dried bamboo tubes and increase their economic value - Tiancheng Yuan; Yuan Feng; Tao Zhang; Wenkai Zhu; Yu Wang; Xinzhou Wang; Yanjun Li (Journal of Cleaner Production, 2025)

Lipid-involved browning mechanism during the drying process of squid - Junpeng Zeng; Yu Song; Xiaowei Fan; Yanjun Liu; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Iron-doped titanium lithium-ion Sieves@Sodium alginate-enhanced carboxymethyl cellulose aerogels: A synergistic leap in adsorption and sustainability - Shengkai Liu; Birong Yan; Yu Han; Wei Wang; Yimin Shi; Yonggui Wang; Huiling Li; Junhao Liu; Zefang Xiao; Daxin Liang; Yanjun Xie (Journal of Cleaner Production, 2025)

A new analysis of an application of low-carbon pre-selecting technology (LCPT) for minerals: An evolutionary game model among stakeholders - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Journal of Cleaner Production, 2025)

Mechanisms by which Ganglioside GM1, a specific type of glycosphingolipid, ameliorates BMAA-induced neurotoxicity in early-life stage of zebrafish embryos - Yanjun Liu; Yuhe Zhu; Xiaoxu Wang; Yiyang Li; Shuaiqi Yang; Hongyan Li; Bo Dong; Zhigao Wang; Yu Song; Jie Xu; Changhu Xue (Food Research International, 2025)

The digestive behavior of pectin in human gastrointestinal tract: a review on fermentation characteristics and degradation mechanism - Weichao Cao; Shuyi Guan; Yuying Yuan; Yuhang Wang; Yiasmin Mst Nushrat; Yaxian Liu; Yanjun Tong; Shuhuai Yu; Xiao Hua (Critical Reviews in Food Science and Nutrition, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Freeze-thaw aging increases the toxicity of microplastics to earthworms and enriches pollutant-degrading microbial genera - Yanjun Li; Guanghui Xu; Jian Wang; Yong Yu (Journal of Hazardous Materials, 2024)

Effect of cytochrome c release on the mitochondrial-dependent apoptosis and quality deterioration of black rockfish (Sebastes schlegelii) postmortem storage - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Establishment of a standardized daily behavior collection and analysis system for brain disease models of rhesus and cynomolgus monkeys and its application in autism spectrum disorder - Xiaofeng Ren; Huimin Wang; Xiaoman Lv; Yi Zhou; Yingyin Fan; Yanjun Yu; Christoph W. Turck; Yuhui Chen; Longbao Lv; Yingzhou Hu; Hao Li; Wenchao Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)
Complex brain diseases seriously endanger human health, and early diagnostic biomarkers and effective treatments are currently lacking. Due to ethical constraints on human research, establishing monkey models is crucial to address these issues. With the rapid development of technology, transgenic monkey models of a range of brain diseases, especially autism spectrum disorder (ASD), have been successfully established. However, to establish practical and effective brain disease models and subsequently apply them to disease mechanism and treatment studies, there is still a lack of a standard tool, i.e., a system for collecting and analyzing the daily behaviors of brain disease model monkeys. Therefore, with the goal of undertaking a comprehensive and quantitative study of behavioral phenotypes, we established a standard daily behavior collection and analysis system, including behavioral data collection protocols and a monkey daily behavior ethogram (MDBE) for rhesus and cynomolgus monkeys, which are the most commonly used non-human primates in model construction. Then, we used ASD as an application example after referring to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), which is widely used in clinical disease diagnosis to obtain ASD core clinical symptoms. We then established a sub-ethogram (ASD monkey core behavior ethogram (MCBE-ASD)) specifically for quantitative assessment of the core clinical symptoms of an ASD monkey model based on MDBE. Subsequently, we demonstrated the high reproducibility of the system.

Enhanced co-pyrolysis of textile and leather waste with Ca/Fe-enriched sludge ash: Catalytic effect on thermal behavior, volatile composition, and biochar formation - Yanjun Hu; Zhipeng Xia; Xu Wang; Bo Xing; Qi Chen; Fan Yu; Nan Zhou (Fuel, 2024)

Chemical fertilizers promote dissemination of ARGs in maize rhizosphere: An overlooked risk revealed after 37-year traditional agriculture practice - Xiaolong Lin; Guanghui Xu; Yanjun Li; Yong Yu (Science of The Total Environment, 2024)

A novel selective collector MIBATC and its performance on flotation separation of chalcopyrite from sphalerite and pyrite - Xuesong Sun; Jianwen Yu; Yanjun Li; Yuexin Han; Peng Gao (Minerals Engineering, 2024)

Regrowth or smart decline? A policy response to shrinking cities based on a resilience perspective - Yu Jin; Guolei Zhou; Hongri Sun; Hui Fu; Hanchun Wu; Yanjun Liu (Sustainable Cities and Society, 2024)

Review of non-isothermal processes in CCUS from a geomechanical perspective - Shuaiyi Lu; Ziwang Yu; Yanjun Zhang; Tianfu Xu (Earth-Science Reviews, 2024)

Modification with lignin-based N-P flame retardant to improve the flame retardancy and smoke suppression of wood - Fanjun Yu; Zhichen Ba; Zhizun Gao; Yonggui Wang; Yanjun Xie; Haigang Wang; Zhe Qiu; Zefang Xiao (Chemical Engineering Journal, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

New approach to reduce carbon emissions by hydrogen reduction of boron-bearing iron concentrate in a fluidized bed: Reduction kinetics and microstructure analysis - Peiyu Li; Jianwen Yu; Yanjun Li; Peng Gao; Yuexin Han (Minerals Engineering, 2024)

Ultrafine Pt particles on hollow hierarchical porous β zeolites for selective hydrogenation of naphthalene - Zhentao Liu; Jinlin Mei; Dandan Wang; Xiaoyang Kong; Ke Yu; Zhengkai Cao; Chunya Wang; Yanjun Gong; Aijun Duan; Chunming Xu; Xilong Wang (Fuel, 2024)

Hydrothermally Ce modified HZSM-5 zeolite enhancing its strong acidity and Brønsted/Lewis acid ratio: Stably boosting ethylene/propylene ratio for cracking n-heptane - Qi Liu; Zhengkang Yang; Zikang Chen; Peng Xiao; Yafen Ge; Yu Piao; Yanjun Gong (Fuel, 2024)

In vitro and in vivo activity of ceftazidime/avibactam and aztreonam alone or in combination against mcr-9, serine- and metallo-β-lactamases–co-producing carbapenem-resistant Enterobacter cloacae complex - Wengang Li; Jisheng Zhang; Yanjun Fu; Jianmin Wang; Longjin Liu; Wenzhang Long; Kaixin Yu; Xinhui Li; Chunli Wei; Xushan Liang; Jin Wang; Chunjiang Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Riboflavin alleviates the occurrence of anthracnose caused by Colletotrichum gloeosporioides in postharvest mango and the possible mechanisms involved - Mingtao Zhu; Zhuanying Yang; Neng Wang; Liangjie Chen; Yanjun Xiao; Lijun Yu; Chunyan Long; Xinjie Yang; Jun Yu (Food Bioscience, 2024)

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)

Soil pH is the Primary Factor Driving the Transformation of Plant Cuticular Wax in Saline Soils - Jianfeng Yang; Tianyu Wang; Yingpeng Sun; Yu Ni; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2024)

Freeze-thaw aged polyethylene and polypropylene microplastics alter enzyme activity and microbial community composition in soil - Yanjun Li; Guanghui Xu; Yong Yu (Journal of Hazardous Materials, 2024)

Valorization of waste graphite in spent lithium-ion batteries to graphene via modified mechanical exfoliation and the mechanism exploration - Yanjun Liu; Jiadong Yu; Yukun Zhao; Jiarui Lai; Jinhui Li; Quanyin Tan (Journal of Cleaner Production, 2024)

Bioavailability transition path of phosphorus species during the sewage sludge incineration process - Qianqian Guo; Yanan Wang; Lingqin Zhao; Fan Yu; Zehuang Zhang; Nan Zhou; Long Jiao; Yanjun Hu (Environmental Research, 2024)

Optimization of CO2 sequestration in alkaline industrial Residues: The enhancement mechanism of saline soil - Jianguo Kang; Ziwang Yu; Yanjun Zhang; Tianfu Xu; Liangliang Guo; Shuren Hao (Chemical Engineering Journal, 2024)

Ethylene thiourea exposure induces neurobehavioral toxicity in zebrafish by disrupting axon growth and neuromuscular junctions - Jingming Wang; Zhiquan Yu; Yongfeng Wang; Yuanyao Chen; Lin Xiao; Yanjun Zong; Qiyuan Feng; Lianqi Peng; Huiping Zhang; Chunyan Liu (Journal of Environmental Sciences, 2024)

A comparison of hydrothermal carbonization versus pyrolysis-activation for sludge-derived carbon materials on physiochemical properties and electrochemical performance - Qianqian Guo; Shixuan Qiao; Dongming Zhang; Zehuang Zhang; Fan Yu; Zhongqing Ma; Yanjun Hu (Biomass and Bioenergy, 2024)

The cuticular wax on sorghum straw influenced soil microbial diversity and straw degradation in soil - Daixiang Xu; Cai Qi; Jianfeng Yang; Yu Ni; Yanjun Guo (Applied Soil Ecology, 2024)

Adsorption behaviors and atomistic mechanisms of iodate and iodide on hollow spherical allophane nanoparticles - Shun Wang; Yanjun Zhang; Dong Liu; Peng Yuan; Mengyuan Li; Peixin Du; Jinkui Zhao; Wenbin Yu; Howard Wang (Applied Clay Science, 2024)

Cobalt etched graphite felt electrode for enhanced removal of organic pollutant in aqueous solution with a solid polymer electrolyte - Xinyu Li; Yanjun Yu; Ruijuan Zhang; Weilin Guo (Environmental Science and Pollution Research, 2024)

Effects and mechanisms of polystyrene micro- and nano-plastics on the spread of antibiotic resistance genes from soil to lettuce - Guanghui Xu; Yanjun Li; Xiaolong Lin; Yong Yu (Science of The Total Environment, 2024)

PhenoNet: A two-stage lightweight deep learning framework for real-time wheat phenophase classification - Ruinan Zhang; Shichao Jin; Yuanhao Zhang; Jingrong Zang; Yu Wang; Qing Li; Zhuangzhuang Sun; Xiao Wang; Qin Zhou; Jian Cai; Shan Xu; Yanjun Su; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Ocular topical application of alpha-glucosyl hesperidin as an active pharmaceutical excipient: in vitro and in vivo experimental evaluation - Linrong Yu; Qiliang Zhang; Liping Zhou; Yanjun Wei; Mengshuang Li; Xianggen Wu; Meng Xin (Drug Delivery and Translational Research, 2024)

Toxic effects and mechanisms of engineered nanoparticles and nanoplastics on lettuce (Lactuca sativa L.) - Yanjun Li; Xiaolong Lin; Guanghui Xu; Qiuliang Yan; Yong Yu (Science of The Total Environment, 2024)

Ultra-stretchable, sensitive and breathable electronic skin based on TPU electrospinning fibrous membrane with microcrack structure for human motion monitoring and self-powered application - Yu Tian; Mengjie Huang; Yalong Wang; Yanjun Zheng; Rui Yin; Hu Liu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Housing vacancy identification in shrinking cities based on multi-source data: A case study of Fushun city in Northeast China - Hongri Sun; Guolei Zhou; Yanjun Liu; Hui Fu; Yu Jin (Journal of Geographical Sciences, 2024)

Will the ‘evapotranspiration paradox’ phenomenon exist across China in the future? - Zhenjie Li; Buda Su; Miaoni Gao; Hui Tao; Shan Jiang; Yu Gong; Yanjun Wang; Jian Zhou; Tong Jiang (International Journal of Climatology, 2023)
The uneven changes in potential evapotranspiration (PET) in response to temperature rise are called the ‘evapotranspiration paradox’ phenomenon, which is expected to intensify further under a warming climate. In this paper, we explored the spatial–temporal changes in the future ‘evapotranspiration paradox’ phenomenon over China and its 10 major river sub‐regions under different climate change scenarios. Thus, this paper uses four global climate model outputs under seven shared socioeconomic pathway‐based scenarios (SSP1‐1.9, SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, SSP4‐3.4, SSP4‐6.0 and SSP5‐8.5) from the sixth phase of the Coupled Model Intercomparison Project (CMIP6). Considering the latest IPCC's 6th Assessment Report (AR6), this research emphasizes the 2021–2040 (near‐term), 2041–2060 (mid‐term) and 2081–2100 (long‐term) periods to anticipate the ‘evapotranspiration paradox’ phenomenon. In this study, PET is estimated based on the modified Penman–Monteith (P‐M) method (considering CO 2 ). Furthermore, the paradox phenomenon in this study is defined considering two pivotal conditions: the surface temperature increases but the evaporation decreases (Type I), and the temperature decreases but the evaporation still tends to increase (Type II). The results show that there were only Type I ‘evapotranspiration paradoxes’ that existed in the historical period, which were dominant especially before the 1990s. Nearly 50% of the areas experienced the Type I ‘evapotranspiration paradox’ phenomenon that occurred during 1975–1994 and 1995–2014. Spatially, it covered 100% of the area of the Southeast River (SER) and the Liaohe River (LR) during 1975–1994 and the area of the SER, the HAR, the HHR and the LR during 1995–2014. In the future, the interdecadal growth rate of PET in China is projected to be the highest under the SSP5‐8.5 and the lowest under the SSP3‐7.0 with spatial variation. Importantly, the largest areas of approximately 36% and 45% with the Type I phenomenon are inclined to occur under the SSP1‐1.9 and SSP4‐6.0, respectively, over the long‐term period (2081–2100). The area with the Type I phenomenon will be less than 20% in the near‐term, and it is less than 12% in the mid‐term period. For the Type II evapotranspiration paradox, the uppermost 45% of the area is expected to experience the Type II phenomenon under SSP1‐1.9 during the mid‐term period, while it is 30% under SSP1‐2.6 during the long‐term period. However, this study's findings provide the scientific basis for formulating adaptation and mitigation strategies to combat ‘evapotranspiration paradox’‐related extremes at regional scales.

Enhanced electrocatalytic degradation of acid orange 7 by using double perovskite La2CoxNi1-xMnO6/nickel foam as the electro-Fenton cathodes - Ruijuan Zhang; Xinyu Li; Yanjun Yu; Weilin Guo (Journal of Water Process Engineering, 2023)

Failure process and mechanism analysis of rock slope induced by underground mining: a case study in Yanqianshan open-pit mine, China - Lingfei Zhang; Zhonghui Chen; Zihan Zhou; Jianshuai Hao; Yu Zhou; Yanjun Shen (Bulletin of Engineering Geology and the Environment, 2023)

Mass-based trophic transfer of polystyrene nanoplastics in the lettuce-snail food chain - Yanjun Li; Xiaolong Lin; Jian Wang; Guanghui Xu; Yong Yu (Science of The Total Environment, 2023)

Achieving grain security and carbon neutrality: Challenges from carbon allocation - Fan Liu; Yucui Zhang; Xingchang Wang; Yongqing Qi; Leilei Min; Guirui Yu; Chunsheng Hu; Yanjun Shen (Journal of Cleaner Production, 2023)

Effect of straw return on soil respiration in dryland agroecosystem of China: A meta-analysis - Yanjun Zhang; Junliang Zou; Bruce Osborne; Wei Dang; Yuxia Xu; Yuanyuan Ren; Shuina Dang; Lijuan Wang; Xi Chen; Yuan Yu (Ecological Engineering, 2023)

A pilot study on recovery of iron from sulfur-bearing hematite ore using hydrogen-based mineral phase transformation followed by magnetic separation - Jianwen Yu; Hao Sun; Peiyu Li; Wenjie Han; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2023)

Highly sensitively detection of amine vapors released during shrimp spoilage by fluorescent molecules locked in covalent organic frameworks - Jingru Mi; Yongxian Guo; Yanjun Gong; Shuya Liu; Mei Zhao; Qiongzheng Hu; Li Yu (Food Chemistry, 2023)

Gene-environment interaction in long-term effects of polychlorinated biphenyls exposure on glucose homeostasis and type 2 diabetes: The modifying effects of genetic risk and lifestyle - Qiyou Tan; Shijie Yang; Bin Wang; Mengyi Wang; Linling Yu; Ruyi Liang; Wei Liu; Jiahao Song; Yanjun Guo; Min Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Development of the thermophysical parameter tester for measuring the soil matrix suction and optimization of the calibration function - Jianguo Kang; Ziwang Yu; Yanjun Zhang; Tong Zhang; Peiyi Yao; Xiaoqi Ye (Computers and Electronics in Agriculture, 2023)

High performance and mechanism of Tl(I) removal from solution by synergetic application of nanowire γ-MnOOH@biochar and free radicals: Implications to AMD treatment - Jin Wang; Shan Yu; Yanjun Jiang; Yanyi Liu; Xinni Xiong; Jun Xiao; Mengqing Sun; Jingzi Beiyuan; Juan Liu; Gang Song (Journal of Water Process Engineering, 2023)

Artificial potential incorporated adaptive fixed-time sliding mode control for target capture - Bicheng Cai; Cheng Wei; Chengfei Yue; Yanjun Yu; Xueqin Chen; Yunhai Geng (Advances in Space Research, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Comparative study of sediment phosphorus immobilization via the addition of lanthanum-modified and thermal-modified drinking water treatment sludge - Fei Sun; Yu Chen; Liwenze He; Jingxiang Tang; Yanjun Li (Environmental Science and Pollution Research, 2023)

Does forest farm carbon sink projects affect agricultural development? Evidence from a Quasi-experiment in China - Jian Liu; Yanjun Ren; Yu Hong; Thomas Glauben (Journal of Environmental Management, 2023)

Numerical study of hydraulic fracturing treatments and geothermal energy extraction from a naturally fractured granitic formation - Zhihong Lei; Yanjun Zhang; Shikun Zhang; Yu Shi (Geothermics, 2023)

Lipidomics approach in alcoholic liver disease mice with sphingolipid metabolism disorder: Alleviation using sea cucumber phospholipids - Zhigao Wang; Xiaoxu Wang; Yuliu Wang; Yanjun Liu; Xincen Wang; Yu Song; Jie Xu; Changhu Xue (Food Bioscience, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Diversified chemical profiles of cuticular wax on alpine meadow plants of the Qinghai-Tibet Plateau - Jianfeng Yang; Lucas Busta; Reinhard Jetter; Yingpeng Sun; Tianyu Wang; Wenlan Zhang; Yu Ni; Yanjun Guo (Planta, 2023)

Microstructure damage characteristics and its mechanism of undisturbed loess suffering to weak acid leaching - Lei Zhang; Ruixin Yan; Jianbing Peng; Yanjun Shen; Jinyuan Zhang; Yu Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Verticillium dahliae Asp1 regulates the transition from vegetative growth to asexual reproduction by modulating microtubule dynamic organization - Juan Tian; Mengli Pu; Bin Chen; Guangda Wang; Chunli Li; Xiaxia Zhang; Yanjun Yu; Zhi Wang; Zhaosheng Kong (Environmental Microbiology, 2023)
Verticillium dahliae is a devastating pathogenic fungus that causes severe vascular wilts in more than 400 dicotyledonous plants. The conidiation of V. dahliae in plant vascular tissues is the key strategy for its adaptation to the nutrient‐poor environment and is required for its pathogenicity. However, it remains unclear about the regulatory mechanism of conidium production of V. dahliae in vascular tissues. Here, we found that VdAsp1 , encoding an inositol polyphosphate kinase, is indispensable for the pathogenicity of V. dahliae . Loss of VdAsp1 function does not affect the invasion of the host, but it impairs the colonization and proliferation in vascular tissues. The Δ VdAsp1 mutant shows defective initiation of conidiophore formation and reduced expression of genes associated with the central developmental pathway. By live‐cell imaging, we observed that some of Δ VdAsp1 mutant hyphae are swollen, and microtubule arrangements at the apical region of these hyphae are disorganized. These results indicate that VdAsp1 regulates the transition from vegetative growth to asexual reproduction by modulating microtubule dynamic organization, which is essential for V. dahliae to colonize and proliferate in vascular tissues. These findings provided a potential new direction in the control of vascular wilt pathogen by targeting conidium production in vascular tissues.

Enhancing streamflow simulation using hybridized machine learning models in a semi-arid basin of the Chinese loess Plateau - Qiang Yu; Liguang Jiang; Yanjun Wang; Junguo Liu (Journal of Hydrology, 2023)

A case study on the migration of nuclides in the coupled vadose zone-groundwater system at a proposed spent fuel reprocessing site in Gansu, China - Xin Zhang; Yanjun Zhang; Yu Zhang; Xuefeng Gao; Yuxiang Cheng; Yongjie Ma; Peng Zhang; Xuhong Wang (Journal of Hydrology, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Application of machine learning in carbon capture and storage: An in-depth insight from the perspective of geoscience - Peiyi Yao; Ziwang Yu; Yanjun Zhang; Tianfu Xu (Fuel, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.

Cobalt induces neurodegenerative damages through impairing autophagic flux by activating hypoxia-inducible factor-1α triggered ROS overproduction - Jianping Tang; Yanjun Li; Xu Liu; Guangxia Yu; Fuli Zheng; Zhenkun Guo; Yating Zhang; Wenya Shao; Siying Wu; Huangyuan Li (Science of The Total Environment, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Hollowing of nanoparticle membrane by sacrificing phase-inversion-formed nanohydrogel to enhance solar–steam generation efficiency - Yu Ma; Xiaoli Zhao; Yanjun Shen; Yi Wang; Bin He (Desalination, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

Elucidating the origin mechanism of a morphology-dependent layered double hydroxide catalyst toward organic contaminant oxidation via persulfate activation - Rongyao Wang; Yanjun Yu; Ruijuan Zhang; Xiaohua Ren; Weilin Guo (Environmental Science and Pollution Research, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Effects of inhomogeneity on mechanical properties of granites in Songliao Basin using the grain-based model - Tianrui Yang; Ziwang Yu; Yanjun Zhang; Jianguo Kang; Xiaoqi Ye; Chaohui Yan (Arabian Journal of Geosciences, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Two new benzoic acid derivatives from endophytic fungus Aspergillus versicolor - Yanqing Ye; Yanjun Chen; Yuting Hou; Hongmei Yu; Lijun Zhu; Yanqi Sun; Min Zhou; Yijian Chen; Miao Dong (Natural Product Research, 2022)

Investigation on Reservoir Stimulation Characteristics in Hot Dry Rock Geothermal Formations of China During Hydraulic Fracturing - Yuxiang Cheng; Yanjun Zhang; Ziwang Yu; Zhongjun Hu (Rock Mechanics and Rock Engineering, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Application of deep learning in ecological resource research: Theories, methods, and challenges - Qinghua Guo; Shichao Jin; Min Li; Qiuli Yang; Kexin Xu; Yuanzhen Ju; Jing Zhang; Jing Xuan; Jin Liu; Yanjun Su; Qiang Xu; Yu Liu (Science China Earth Sciences, 2020)

Rhizobial infection triggers systemic transport of endogenous RNAs between shoots and roots in soybean - Chen Zhang; Meifang Qi; Xiaxia Zhang; Qi Wang; Yanjun Yu; Yijing Zhang; Zhaosheng Kong (Science China Life Sciences, 2020)

Genome-wide association study of soybean seed germination under drought stress - Zhangxiong Liu; Huihui Li; Zuowang Gou; Yanjun Zhang; Xingrong Wang; Honglei Ren; Zixiang Wen; Beom-Kyu Kang; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Molecular Genetics and Genomics, 2020)

Drought-induced disturbance of carbohydrate metabolism in anthers and male abortion of two Gossypium hirsutum cultivars differing in drought tolerance - Wei Hu; Yanjun Huang; Dimitra A. Loka; Hua Bai; Yu Liu; Shanshan Wang; Zhiguo Zhou (Plant Cell Reports, 2020)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

Follicular helper T cell and memory B cell immunity in CHC patients - Yong Liu; Huifan Ji; Pingwei Zhao; Hongqing Yan; Yanjun Cai; Lei Yu; Xiaoli Hu; Xiguang Sun; Yanfang Jiang (Journal of Molecular Medicine, 2019)

The Interaction of Population, Industry and Land in Process of Urbanization in China: A Case Study in Jilin Province - Yanjun Liu; Guolei Zhou; Degang Liu; Huisheng Yu; Liyuan Zhu; Jing Zhang (Chinese Geographical Science, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

A New Primer to Amplify pmoA Gene From NC10 Bacteria in the Sediments of Dongchang Lake and Dongping Lake - Shenghui Wang; Yanjun Liu; Guofu Liu; Yaru Huang; Yu Zhou (Current Microbiology, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Occurrence and Partitioning of Antibiotics in the Water Column and Bottom Sediments from the Intertidal Zone in the Bohai Bay, China - Dengmiao Cheng; Yujia Xie; Yanjun Yu; Xinhui Liu; Shengnan Zhao; Baoshan Cui; Junhong Bai (Wetlands, 2016)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Variations of cuticular wax in mulberry trees and their effects on gas exchange and post-harvest water loss - Yu Ni; Zhengyuan Sun; Xianzhi Huang; Chuanshu Huang; Yanjun Guo (Acta Physiologiae Plantarum, 2015)

Novel integration strategy coupling codon and fermentation optimization for efficiently enhancing sarcosine oxidase (SOX) production in recombinant Escherichia coli - Yanjun Tong; Hailin Yang; Yu Xin; Ling Zhang; Wu Wang (World Journal of Microbiology and Biotechnology, 2015)

Application of exogenous substances reduces tobacco-specific nitrosamines content by regulating biosynthesis of nicotine and nitrite in burley tobacco - Siwei Liang; Jinpeng Yang; Jun Zhou; Jun Yu; Yanjun Ma; Ruoshi Bai; Fangsen Xu; Chunlei Yang (Acta Physiologiae Plantarum, 2013)

Control of the PI3K/Akt pathway by porcine reproductive and respiratory syndrome virus - Liqian Zhu; Shen Yang; Wu Tong; Jianping Zhu; Hai Yu; Yanjun Zhou; Robert B. Morrison; Guangzhi Tong (Archives of Virology, 2013)

Antisense MMP-9 RNA inhibits malignant glioma cell growth in vitro and in vivo - Cuiyun Sun; Qian Wang; Hongxu Zhou; Shizhu Yu; Alain R. Simard; Chunsheng Kang; Yanyan Li; Yanling Kong; Tongling An; Yanjun Wen; Fudong Shi; Junwei Hao (Neuroscience Bulletin, 2013)

Regeneration of insulin monomers from amyloid fibrils by a NH3/H2O2 two-step method - Rui Liu; Rongxin Su; Yanjun Yu; Wei Qi; Libing Wang; Zhimin He (Biotechnology Letters, 2012)

Prediction of permafrost changes in Northeastern China under a changing climate - Zhi Wei; HuiJun Jin; JianMing Zhang; ShaoPeng Yu; XuJun Han; YanJun Ji; RuiXia He; XiaoLi Chang (Science China Earth Sciences, 2011)

Comparative QSAR modeling of antitumor activity of ARC-111 analogues using stepwise MLR, PLS, and ANN techniques - Yanjun Yu; Rongxin Su; Libing Wang; Wei Qi; Zhimin He (Medicinal Chemistry Research, 2010)

Identification of novel denitrifying bacteria Stenotrophomonas sp. ZZ15 and Oceanimonas sp. YC13 and application for removal of nitrate from industrial wastewater - Lu Yu; Yanjun Liu; Gejiao Wang (Biodegradation, 2009)

Variation of fluxes of water vapor, sensible heat and carbon dioxide above winter wheat and maize canopies - Zhang Yongqiang; Shen Yanjun; Yu Qiang; Liu Changming; A. Kondoh; Tang Changyuan; Sun Hongyong; Jia Jinsheng (Journal of Geographical Sciences, 2002)